Le tango à Buenos Aires et Montevideo : de la globalisation à la valorisation - Sébastien Jacquot (Bulletin de l’Association de Géographes Français)
Tango was born in the Rio de la Plata basin at the end of the 19th century. After an eclipse in the second half of the 20th century, it is experiencing a globalized revival, both as a spectacle and as a practice. To consider the geography of tango in Buenos Aires and Montevideo is then to study their prominent place in a diversity of tourist and cultural circulations, at various scales (continental and global), transforming cultural and heritage elements into territorial symbols and drivers of development through culture and tourism. These political and economic uses of tango pluralize its meanings and produce conflicts on the modes of anchoring a cultural practice to these two cities.